An Obtuse‐angled Corner Unit for Fluctuating Carbon Nanohoops. Issue 2 (21st December 2016) - Sun, Zhe; Miyamoto, Naoya; Sato, Sota; Tokuyama, Hidetoshi; Isobe, Hiroyuki
Abstract: The invention of corner units was the key factor that allowed the synthesis of cyclo‐ para ‐phenylenes with strained curved π‐systems. Despite only a few scarce instances of the development of corner units to date, a variety of structural congeners have been synthesized. These preceding corner units commonly possessed directing angles of ≤90°, which enabled the macrocyclization of multiple units, up to six. In this study, we introduce an obtuse‐angled corner unit for the synthesis of cyclo‐ para ‐phenylene congeners. The corner unit with oxanorbornadiene possessed a directing angle of 126° and thus allowed for the macrocyclization of larger structures with up to seven units. Reductive aromatization was applicable to complete the cyclo‐ para ‐phenylene structures and afforded the congeners with multiple anthracenylene panels. Structural studies with experimental and theoretical methods revealed a fluctuating structure with an intrinsic non‐belt shape. Abstract : Jumping through nanohoops : When opened by a bicyclic structure, a corner unit for nanohoop widens the circle of macrocycles and allows for one‐pot assembly of seven units. A nanohoop with anthracenylene panels was completed by aromatization and demonstrated the presence of fluctuating structures in solution.